Karl Tomm’s Collaborative Approaches to Counselling - Strong, Tom; Sutherland, Olga; Couture, Shari; Godard, Greg; Hope, Tom (Canadian Journal of Counselling and Psychotherapy, 2008)
Karl Tomm, a Canadian psychiatrist and family counsellor, has been at the forefront of developments in collaborative practice with clients for over 25 years. We situate Dr. Tomm’s ideas in relation to counselling, noting some of his important contributions to conceptualizing counsellors’ engagement with clients. We will also depict Tomm’s innovations as dialogic, suggesting that he looks upon his interactions with clients as co-creating accomplishments in the back and forth of therapeutic interaction. We highlight detailed discursive analyses of his actual interviews with clients, illustrating some conversational practices that further collaborative practice. The article concludes by summarizing Tomm’s ideas and conversational practices as they relate to fostering collaborative dialogue with clients.